(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
Motivation plays a critical role in shaping how individuals choose coping strategies to manage stress and adversity. By understanding the underlying motivational factors, one can better predict adaptive or maladaptive coping outcomes. This article explores the types of motivation influencing coping strategies, such as intrinsic and extrinsic motivation, and discusses their implications for stress management. Citing recent research and established psychological theories, the discussion highlights the interplay between motivation and psychological resilience. Additionally, cultural and contextual factors influencing motivational dynamics are examined, shedding light on the complex mechanisms underlying coping behaviors.